UMAR BIN ABDUL AZIS: ZAMAN KEEMASAN ISLAM MASA DINASTI UMAYYAH - Kori Lilie Muslim; Melia Afdayeni (Islam Transformatif : Journal of Islamic Studies, 2019)
The Umayyad dynasty was approximately 91 years old, with 14 leading caliphs. The reign of Umar ibn Azis was regarded as the golden age of the regime, as many of the policies he had done, and that had been prosperity for the people. Different from the governments of the other caliphs, regarded by most historians as the caliphs who made the people in misery. For this, the article aims to analyze the glory achieved by Umar ibn Azis in the reign of the Umayyad dynasty. The methods used are historical research methods, ranging from source search (heuristics) that are limited to historical books in libraries, then criticism of Sember (internal and external criticism), verification and Last is historiography. From the research conducted it can be shown that during the reign of the caliph Umar ibn Abdul Aziz who did not have a long time to print the history of the glorious civilization, both in terms of the knowledge and life level of society that has been able to enjoy Prosperous life is safe and peaceful. The Baitul Mal by the previous Umayyad caliphs was used as a sovereign or property that is free to be spent by the Palace families. It is different in the time of the end of the Umar because at the time of his treasure Baitul Mal made As the people's. Umar bin Abdul Aziz was also very attentive to the hadith as a source of teaching both Islamic teachings. He issued adequate funds to record the hadith to be registered and documented well and neatly and made a scientific reference in religious studies and Islamic legal studies. Not only the hadith that received attention, but the science of interpretation, history, and politics is also recorded. In terms of the expansion of the territory of Islam, very few wars in his time because in the development of Islam is more lively by using the advice that is full of wisdom so that many people enter Islam. Thus the reign of the caliphate of Umar ibn Abdul Aziz, which was the Golden age for the Umayyad dynasty.